PEDAGOGICAL CONDITIONS OF TEACHING “COMPUTER GRAPHICS AND VISUALIZATION ” (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2023)
This in the article pedagogy higher education in institutions Teaching “Computer graphics and visualization”. Pedagogical conditions specified. Also , the computer graph programs using visual projects to prepare about offer and recommendations brought.